Build Your Own Metaverse with Unity A Practical Guide to Developing Your Own Cross-Platform Metaverse with Unity3D and Firebase - Nadales, David Cantón (Packt Publishing, Limited, 2023)
Build Your Own Metaverse with Unity is a practical guide for developers with step-by-step explanations, practical examples, and screenshots to guide them through essential concepts. You’ll start by learning how to install Unity and create a character that can move around the virtual world. Next, you’ll learn how to integrate multiplayer functionality, user identification, and registration in your game universe. You’ll explore how to create interactive characters dealing with different attributes of the virtual world, including acquiring homes and decorating them with various features. Additionally, you’ll understand how to use Firebase tools to make your Metaverse unique. By following the expert advice, you’ll be able to create a feature rich Metaverse where players can interact with NPCs, acquire homes, and interact with other players online. Finally, you’ll discover how to compile and distribute the finished project to various platforms, while acquiring with necessary skills and knowledge to create a unique and groundbreaking Metaverse. By the end of this book, you’ll be well-equipped to create a Metaverse with infinite possibilities.